Dual-model predictive control of two independent induction motors driven by a SiC nine-switch inverter - Gokdag, Mustafa; Gulbudak, Ozan (International journal of electronics, 2023)
This paper presents a finite control set model predictive control (FCS-MPC) approach for two induction machines driven by a nine-switch inverter (NSI). In the traditional approach, two separate voltage source inverters are necessary to drive the independent induction motors. In the proposed method, the nine-switch inverter is used to control the separate motors with a reduced number of switching devices compared to traditional method. A robust control strategy that eliminates the interactions between separate mechanical loads is required to achieve a proper independent speed and torque control for two induction machines through the NSI. To ensure the reliability of the machine operation, the indirect-field oriented control-based model predictive control strategy is proposed. The proposed control strategy is experimentally validated across the 3.2 kW SiC-based NSI prototype. The control algorithm is performed on an Altera Cyclone IV Field-programmable gate array. The experimental results demonstrate that the proposed dual-model predictive control method provides a good and robust motor control operation under different loading conditions. Two induction motors are successfully controlled, and the independent speed and torque control are achieved.